DEVELOPING ENGLISH RESEARCH ARTICLE WRITING GUIDE TEXTBOOK FOR NON-ENGLISH DEPARTMENT STUDENTS USING THE ADDIE MODEL - Isry Laila Syathroh; Siska Rizkiani (Indonesian EFL Journal, 2023)
This study aims to develop a textbook as a guide for writing research articles in English to answer the challenges faced by non-English department students in writing research articles in English. This research applies the R&D (Research and Development) method. The development of this textbook uses the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. In this study, data is collected through questionnaires and interviews. The questionnaires are delivered to 240 students in the non-English department, and interviews are administered with two lecturers at a private higher education institution. A textbook titled "Panduan Penyusunan Karya Ilmiah Berbahasa Inggris" was developed as a result of the development research. The textbook's design and development are heavily impacted by the need analysis results, which determine what will be taught through the textbook. There are several noteworthy discoveries in the evaluation. Despite students' positive responses to the questionnaire statements, implying a certain level of textbook effectiveness, paying attention to the lecturers' conclusions is critical. They noted that the developed textbook needs additional attention concerning its visual components. As a result, it suggests that the developed textbook be improved, focusing on aesthetic features. Furthermore, it is hoped that the results of this study can become a further reference in the preparation of research articles writing in English so that the problems of non-English department students in writing English research articles can be resolved.